IMPROVING A PEDAGOGICAL IMAGE OF AN EDUCATIONAL INSTITUTION: A CASE STUDY - Budnyk, Olena; Vasianovych, Hryhorii; Mikulets, Liudmyla; Avkhutska, Svitlana; Sinitsyna, Alla; Turkov, Volodymyr; Nikolaesku, Inna (Revista Inclusiones, 2021)
The article substantiates the essence and specifics of forming an image of an educational institution while taking into account globalization processes, intensive development of science and technology, expanding opportunities for academic mobility among other factors. The study defines the image of the institution in the context of such concepts as reputation, publicity, identity, public relations and others. The stages of formation of the image of an educational institution are presented. The emphasis is placed on the importance of pedagogical management, which involves the development of the effective interaction strategy among the principal, teaching faculty, students, stake holders and the media to form a positive image of an educational institution. The paper presents the results of the empirical study of the operational characteristics of a personal profile of school principals and their preferred style of communication with the faculty. It has been identified that four types of difficulties are most often encountered by the education managers, among which the most challenging are the development of communicative potential, digitalization of the management process and improvement of personal and professional qualities. It has been found that some education managers can be characterized by the persisting stereotypes based on life experience and management practice; lack of motivation to learn new patterns of behavior and often a conservative approach to management.